2019
DOI: 10.1159/000499743
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneal Hematoma after Bone Marrow Biopsy: The First Cut Should Not Be the Deepest

Abstract: Bone marrow biopsies are standard hematology procedures. We report the case of a patient with acute myeloid leukemia who developed retroperitoneal hematoma after the procedure. The bleeding was stopped with endovascular embolization and coiling. This case raises several issues about the standards for bone marrow biopsies and discusses the approach to patients with bleeding risk factors. We also provide a literature review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Results of bone marrow biopsies following therapy are important, as they guide the treatment plan [27]. When performed by trained personnel, the procedure is safe, but it remains uncomfortable and can be associated with pain and, less often, with bleeding and infections [28][29][30][31][32][33][34][35][36]. In children with AML and in some adult patients with AML, sedation/anesthesia is required for performing the biopsy, and there is always the possibility that the biopsy specimen is not adequate for evaluation [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Results of bone marrow biopsies following therapy are important, as they guide the treatment plan [27]. When performed by trained personnel, the procedure is safe, but it remains uncomfortable and can be associated with pain and, less often, with bleeding and infections [28][29][30][31][32][33][34][35][36]. In children with AML and in some adult patients with AML, sedation/anesthesia is required for performing the biopsy, and there is always the possibility that the biopsy specimen is not adequate for evaluation [37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Only one major bleeding event (0.03%) was recorded in a patient with essential thrombocytosis and a platelet count of >1200 x 10 9 /L at the time of biopsy. Another study showed that from 30 reported cases of major bleeding events following bone marrow biopsy, 6 (20%) were on anticoagulation and 10 (33%) had a diagnosis of MPN 22 . Therefore, available literature, although limited, does not indicate that the use of anticoagulant and/or antiplatelet agents is associated with a strong risk of bleeding in patients undergoing bone marrow biopsy.…”
Section: Management Of Antithrombotic Agentsmentioning
confidence: 99%
“…In addition to the aggregate studies described above, there were approximately 30 case reports that described severe bleeding following BM biopsy. Most (but not all) are summarized by Wojciechowski [6]. Of the case studies, six reported the patient being anticoagulated.…”
Section: Bleeding After Bm Biopsymentioning
confidence: 99%